Israel’s public diplomacy strategies “Hasbara” Case study: Pinkwashing in Israeli Politics - Iriqat, Dalal; Owda, Mahdi (Journal of Ecohumanism, 2025)
This research examines the Israeli strategy of public diplomacy, referred to as “Hasbara,” which Israel uses to shape an international image and reputation to distract attention from its human rights violations against the Palestinians. Public diplomacy serves as a tool for states to influence governments by influencing foreign peoples through branding and selective narratives. Israel has used this success effectively and with huge funding to successfully portray itself as a beacon of democracy in the Middle East, especially through disinformation initiatives and promoting itself as the only supporter in the Middle East and protector of the rights of Palestinian queers and bisexuals to hide its violations against them. This research reveals how public diplomacy works, and in the Israeli case study, how it builds its reputation as a progressive and open society while killing and exterminating Palestinians in the Gaza Strip and violating their rights. Through the descriptive analytical approach, the research examines the Israeli tactics in its public diplomacy, including media campaigns and digital influence, by focusing on marketing the city of Tel Aviv as the gay capital in the region, while it randomly kills Palestinians who may also be gay.In this research paper and in the case study of Israeli pinkwashing, I will evaluate Hasbara in shaping foreign public opinion and how Israel was able to hide colonial policies and manipulate public diplomacy as a propaganda tool.